Formation of emotional culture of future teachers in the process of their professional training and study of the course "History of Pedagogy" (Pedagogy of Higher and Secondary Education, 2011)
The problem of formation of motional culture of the future teachers in the course of their vocational training is investigated in this article. It is specified essence of concept “emotional culture of the person”.
Keywords: emotions; feelings; emotional experiences; emotional culture of the person